Exploration and Practice of Ideological and Political Education in the Basic Course "Public Relations" of Public Utility Management - Zhou, Qing; Wang, Jing; Wang, Miao; Zhu, Xiaorong; Yan, Xu (Journal of Research in Vocational Education, 2024)
This article explores the practice and innovation of ideological and political education in the basic course "Public Relations" of the Public Utility Management major as an example. In the teaching process, teachers delve into the ideological and political elements in the curriculum, combining them with the theoretical knowledge and practical operations of public relations. Through teaching methods such as case analysis, role-playing, and simulation practice, teachers guide students to pay attention to moral and ethical issues in public relations practice, and cultivate their professional ethics and social responsibility. At the same time, teachers also integrate core ideological and political elements such as patriotism, professional ethics, and cultural confidence into the curriculum, guiding students to establish correct values and outlook on life. This article points out the direction for the evaluation of teaching effectiveness, teaching reflection, and teaching improvement of ideological and political courses through actual teaching cases and data.